96 North American taxa sorted – Peck's Hebeloma revisited. (4th March 2022) - Eberhardt, Ursula; Schütz, Nicole; Bartlett, Peter; Beker, Henry J.
ABSTRACT: Charles Horton Peck described some 2700 species of North American fungi in the 19th and early 20th centuries. Among these were 31 species that he described as Hebeloma or that later authors recombined into Hebeloma . These 31 taxa have been analyzed morphologically and molecularly, as far as possible. For six of these species, lectotypes are designated. For twelve species, ITS sequences (some partial) were generated. Thirteen of the species analyzed are Hebeloma, as the genus is delimited today. Of these 13, nine are regarded as 'current', i.e. are names that should be accepted and used. Of the remaining four, three are synonymized with earlier Peck species and one with the generic type H. mesophaeum . Numerous Hebeloma species described from America are synonymized with some of Peck's species, such as H. albidulum, H. album, H. colvinii, H. excedens, H. palustre, H. sordidulum, and H. velatum ; Peck's H. album, H. palustre, and H. velatum are earlier names for H. fragilipes, H. clavulipes, and H. dunense, respectively. All three names were in current use and described from Europe. The 18 species that are not Hebeloma belong to a range of genera: Agrocybe, Hemistropharia, Inocybe, Inosperma, Naucoria, and Pholiota ; three species that were not previously recombined into their respective genera are here recombined and one species, Hebeloma commune is synonymized with Pholiota lenta . Two taxa, that are not Hebeloma, remain unresolved. Sixty later Hebeloma taxa described from North America are revised and synonymized with Peck species and seven with H. mesophaeum, 36 of these supported by ITS (some partial) sequence data. Updates on two species, H. petrakii and H. remyi, from Europe, are also given, and a lectotype and epitype selected for the latter.